Analyzing test results of infusion pumps - Буриченко, Михайло Юрійович; Дворнік, Марина Володимирівна; Іванець, Ольга Борисівна (Technology audit and production reserves, 2014)
The analysis of results of testing infusion pumps, which can be used in resuscitation and delivery rooms of intensive care, in other hospital rooms and when transporting patients, including ambulance cars has been proposed. The differences between actual and given volumes of an injecting solution and speed of its delivery were found. The principles of estimating data accuracy of infusion pumps complying with the international standards were considered. The experimental studies of an infusion pump for checking its operational data reliability were carried out. The calculations by the formulas complying with international standards were made. The prerequisites for developing a risk prediction model when operating infusion pumps were developed. The analysis of the International Electrotechnical Commission standard IEC 60601-1-8 was carried out. Medical electrical equipment Part 1-8: General requirements for basic safety and essential performance – Collateral standard: General requirements, tests and guidance for alarm systems in medical electrical equipment and medical electrical systems.